2023
DOI: 10.1186/s12896-023-00792-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving the regeneration rate of deep lethal mutant protoplasts by fusion to promote efficient L-lysine fermentation

Abstract: Background L-lysine is widely used for feed and special diet products. The transformation of fermentation strains plays a decisive role in the development of these industries. Based on the mutation breeding theory and metabolic engineering methods, this study aimed to improve the regeneration rate of high-lethality protoplasts by combining multiple mutagenesis and homologous cell fusion techniques to efficiently concentrate multiple dominant mutations and optimize the L-lysine production strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The contents of adenosine, biomass, cordycepic acid, cordycepin, total polysaccharides and total triterpenes of the fusants obtained using protoplast fusion of A. cinnamomea and C. militaris were significantly increased [34]. These results showed that the use of protoplast fusion technology to recombine the nucleus and cytoplasm of parents can significantly increase the content of active substances [46,47].…”
Section: Discussionmentioning
confidence: 78%
“…The contents of adenosine, biomass, cordycepic acid, cordycepin, total polysaccharides and total triterpenes of the fusants obtained using protoplast fusion of A. cinnamomea and C. militaris were significantly increased [34]. These results showed that the use of protoplast fusion technology to recombine the nucleus and cytoplasm of parents can significantly increase the content of active substances [46,47].…”
Section: Discussionmentioning
confidence: 78%